Jesus and the Jewish festivals - Burge, Gary M., 1952- (Grand Rapids, Mich. : Zondervan, 2012)
"Christian readers of the New Testament study the great stories about Jesus through the lens of western culture. In this series of books, Gary Burge uses his extensive knowledge of the first century world and the Middle East to offer insights not available to the average person. Each book will develop important cultural themes and wrap them around well-known New Testament passages. And the result will be insights rarely gained elsewhere. Observe how Jesus celebrated the great festivals of Judaism. In each of the six accounts, you will explore the Jewish festival as it was celebrated in the first century and then examine how Jesus used the imagery of the festival to unveil his own mission. Explore the Jewish Sabbath, Passover, Tabernacles, and Hanukkah as Jesus knew them." -- Publisher's description.
The festivals of Judaism -- Jesus and the Sabbath: John 5:1-47 -- Jesus and the Passover: John 6:1-71 -- Jesus and Tabernacles: John 7-9 -- Jesus and Hanukkah: John 10 -- Jesus and his final Passover: John 13-19 -- The early Christians and the Jewish festivals: Acts 1-2, Hebrews 9-10.
Includes bibliographical references (pages 137-139).
Keywords: Jesus Christ -- Person and offices; Fasts and feasts -- Judaism; Fasts and feasts in the Bible; Bible. -- Criticism, interpretation, etc